Ultrahydrophobic fluorous metal-organic framework derived recyclable composite as apromising platform to tackle marine oil spills - Mukherjee, Soumya; Kansara, Ankit M.; Saha, Debasis; Gonnade, Rajesh; Mullangi, Dinesh; Manna, Biplab; Desai, Aamod V.; Thorat, Shridhar H.; Singh, Puyam S.; Mukherjee, Arnab; Ghosh, Sujit K. (Chemistry-A European Journal, 2016)
Derived from a strategically chosen hexafluorinated dicarboxylate linker aimed at the designed synthesis of a superhydrophobic metal-organic framework (MOF), the fluorine-rich nanospace of a water-stable MOF (UHMOF-100) exhibits excellent water-repellent features. It registered the highest water contact angle (approximate to 176 degrees) in the MOF domain, marking the first example of an ultrahydrophobic MOF. Various experimental and theoretical studies reinforce its distinc-tive water-repellent characteristics, and the conjugation of superoleophilicity and unparalleled hydrophobicity of a MOF material has been coherently exploited to achieve real-time oil/water separation in recyclable membrane form, with significant absorption capacity performance. This is also the first report of an oil/water separating fluorinated ultrahydrophobic MOF-based membrane material, with potential promise for tackling marine oil spillages.

Arresting an unusual amide tautomer using divalent cations - Kashid, Somnath M.; Singh, Reman K.; Kwon, Hyejin; Kim, Yung Sam; Mukherjee, Arnab; Bagchi, Sayan (Journal of Physical Chemistry B, 2019)
Ion-specific effects on peptides and proteins are key to biomolecular structure and stability. The subtle roles of the cations are far less understood, compared to the pronounced effects of the anions on proteins. Most importantly, divalent cations such as Ca2+ and Mg2+ are crucial to several biological functions. Herein, we demonstrate that an amide-iminolate equilibrium is triggered by the binding of the divalent cations to the amide oxygen in aqueous solution. The excellent agreement between the experimental and theoretical results confirms the arrest of an unusual amide tautomer by the divalent cations, which is a rarely known phenomenon that might open up an array of applications in chemistry and biology.

Reply to “comment on ‘arresting an unusual amide tautomer using divalent cations’” - Kashid, Somnath M.; Singh, Reman K.; Kwon, Hyejin; Seol, Jin Gyu; Kim, Yung Sam; Mukherjee, Arnab; Bagchi, Sayan (Journal of Physical Chemistry B, 2020)
In our publication, we assigned the blue-shifted shoulder of N-methylacetamide (NMA) in the infrared (IR) spectrum (∼1645 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1) to an iminolate tautomer stabilized in the presence of divalent metal cations (e.g., 5 M Ca<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">2+).<a class="ref ref1" style="outline: none; background-color: transparent; text-decoration-line: underline; color: rgb(26, 13, 171); transition: color 0.3s ease 0s; overflow-wrap: break-word; word-break: break-word; display: inline-block; font-family: Roboto, arial, sans-serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">(1) Cremer and co-workers comment that this shoulder arises from the dehydration of the amide oxygen upon interaction with the metal cations.<a class="ref ref1a ref2" style="outline: none; background-color: transparent; text-decoration-line: underline; color: rgb(26, 13, 171); transition: color 0.3s ease 0s; overflow-wrap: break-word; word-break: break-word; display: inline-block; font-family: Roboto, arial, sans-serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">(2,3) Their assignment is based on three interesting experimental observations: (1) the IR spectrum of <span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">15N-isotope-labeled NMA does not show any considerable red-shift compared to that of NMA; (2) a new peak appears for NMA at 1680 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1 in the presence of 1 M DCl, which shows a 17 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1 red-shift for <span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">15N-labeled NMA; and (3) the IR spectrum of acetone C═O stretch also demonstrates a blue-shifted shoulder in the presence of a high concentration of CaCl<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">2.

Water-controlled keto-enol tautomerization of a prebiotic nucleobase - Datar, Avdhoot; Paithankar, Harshad; Deb, Pranab; Chugh, Jeetender; Bagchi, Sayan; Mukherjee, Arnab; Hazra, Anirban (Journal of Physical Chemistry B, 2022)
Barbituric acid is believed to be a proto-RNA nucleobase that was used for biological information transfer on prebiotic earth before DNA and RNA in their present forms evolved. Nucleobases have various tautomeric forms and the relative stability of these forms is critical to their biological function. It has been shown that barbituric acid has a tri-keto form in the gas phase and an enol form in the solid state. However, its dominant tautomeric form in aqueous medium that is most relevant for biology has been investigated only to a limited extent and the findings are inconclusive. We have used multiple approaches, namely, molecular dynamics, quantum chemistry, NMR, and IR spectroscopy to determine the most stable tautomer of barbituric acid in solution. We find a delicate balance in the stability of the two tautomers, tri-keto and enol, which is tipped toward the enol as the extent of solvation by water increases.